1994
DOI: 10.1159/000247080
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoleucodystrophy: Dermatological Findings and Skin Surface Lipid Study

Abstract: X-linked adrenoleucodystrophy (ALD) is a rare disorder of the very-long-chain fatty acid (VLCFA) metabolism. Cutaneous findings observed in a 29-year-old man included patchy non-cicatricial alopecia of the scalp, intense oily seborrhoea of the head, mild dry-scaling ichthyosis-like appearance of the trunk and legs and pseudo-acanthosis nigricans of the folds. Scanning electron-microscopic examination of the scalp hair showed trichorrhexis-nodosa-like fractures and several structural anomalies of the hair shaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Ichthyosis-like scaling was found in the patient of Papini et al [8], which has not been reported in other cases with Xlinkcd ALD. Interestingly, in Refsum's disease, character ized by a deficiency in the a-hydroxylation of fatty acids with accumulation of phytanic acid, ichthyosis is an impor tant dermatological finding.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…Ichthyosis-like scaling was found in the patient of Papini et al [8], which has not been reported in other cases with Xlinkcd ALD. Interestingly, in Refsum's disease, character ized by a deficiency in the a-hydroxylation of fatty acids with accumulation of phytanic acid, ichthyosis is an impor tant dermatological finding.…”
mentioning
confidence: 70%
“…Hyperseborrhea and sebaceous gland hypertrophy are other features of the case of ALD presented by Papini et al [8]; whether these might be related to the abnormal lipid metabolism in the skin, to the neurologic disturbances or to some alteration in adrenal hormones remains un known. ALD is a rare inborn error of lipid metabolism that should call the attention of dermatologists to peroxisomal function.…”
mentioning
confidence: 88%
See 3 more Smart Citations